2017
DOI: 10.1097/md.0000000000006677
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating osteoporotic fracture risk with the Fracture Risk Assessment Tool in Chinese patients with rheumatoid arthritis

Abstract: This study aims to evaluate the discriminative and predictive capacity of the Fracture Risk Assessment Tool (FRAX) to determine the 10-year risk of osteoporotic fracture in Chinese rheumatoid arthritis (RA) patients.This study included 168 RA patients and 168 healthy individuals as controls. The Chinese mainland FRAX model was applied to calculate the 10-year risk of osteoporotic fractures, defined as fracture of the spine, forearm, hip, or shoulder.The incidence of osteoporosis was significantly increased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 24 publications
5
14
0
2
Order By: Relevance
“…Disease activity predicts bone loss in early RA [ 31 ]. Moreover, the risk of osteoporotic fractures was positively correlated with the DAS28 [ 32 ]. Differences in patients’ characteristics may also contribute to the discrepancy in the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Disease activity predicts bone loss in early RA [ 31 ]. Moreover, the risk of osteoporotic fractures was positively correlated with the DAS28 [ 32 ]. Differences in patients’ characteristics may also contribute to the discrepancy in the study results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RA is now considered one of the most common secondary causes of osteoporosis and bone densitometry should be performed routinely in patients with RA. Previous epidemiologic studies showed that patients with RA have a higher prevalence of osteoporosis and higher incidence of vertebral and nonvertebral fracture as compared with the general population, [ 4 7 ] contributing to considerable morbidity and mortality as well as medical and societal cost. In particular, the 1-year cumulative mortality rate due to hip fracture in RA patients was reported to be approximately 20% and significantly higher than that in general population.…”
Section: Introductionmentioning
confidence: 99%
“…After adding BMD index to FRAX, the 10-year risk of osteoporotic fracture in Chinese RA patients was higher. [ 18 ] This suggests that the selection of BMD markers is of significance in predicting the progression of bone injury in patients. In the treatment of RA, the use of disease-controlling of anti-rheumatic drugs and anti-osteoporotic agents combined with other biological agents to improve systemic osteoporosis is an effective treatment to control the progression of bone injury in patients with RA.…”
Section: Discussionmentioning
confidence: 99%